Effects of tool tilt angle on the in-process heat transfer and mass transfer during friction stir welding. (October 2018) - Zhang, Shuai; Shi, Qingyu; Liu, Qu; Xie, Ruishan; Zhang, Gong; Chen, Gaoqiang
Graphical abstract: Highlights: A geometrical model and an incomplete contact boundary condition are proposed. Three effects of tool tilt angle on the heat and mass transfer in FSW are concluded. An effective method on the characterization of plastic flow field is proposed. Abstract: Tool tilt angle in friction stir welding (FSW) is an important factor that influences the joint quality, but the underlying mechanism has not been fully understood due to the lack of in-process observation. In this study, we present a CFD model, in which a geometrical model and an incomplete contact boundary condition are proposed, to investigate the effects of tool tilt angle on the in-process heat transfer and mass transfer during FSW. Three effects of tool tilt angle on heat transfer and mass transfer have been concluded based on the simulation results. First, a higher temperature is generated by the tilt welding tool on the advancing side (AS), which is attributed to the incomplete contact at the shoulder/workpiece interface. Second, the tilt welding tool generates a higher frictional force at the tool/workpiece interface, which significantly improves the interfacial material flow velocity behind the tool. Third, the tilt welding tool generates a stronger stirring action to the material in the vicinity of the welding tool, which is beneficial for the mixing of materials and the formation of friction stir welds. The approaches and concepts in this study can be used for the optimization of the application of tool tilt angle in FSW.